Understanding the ethnic inequality of the Thai Lao through perspectives on promoting social inclusion policy in Thailand in accordance with UN Sustainable Development Goal 10.2. (4th March 2022) - Draper, John; Kamnuansilpa, Peerasit; Streckfuss, David
ABSTRACT: This article presents one of the first attempts to understand UN Sustainable Development Goal 10.2 (UNSDG 10.2) on reducing inequality as applied to a major ethnic minority community via a simultaneous application of three theoretical aspects of inclusion theory, itself an extension of social justice theory, i.e. via social, economic, and political inclusion. Thailand, recently under military rule for five years, experiences extreme differences in horizontal structural inequalities by ethnicity. These developmental differences, unacknowledged by the Thai state, nonetheless affect state-minority relations, particularly the relationship between the dominant Central Thai ethnic community and the Thai Lao (TL) ethnic community. The general policy prescription to address such inequalities by ethnicity is to promote greater inclusion, as in UNSDG 10.2. As the state does not properly recognise the TL, this is problematic. This study applied a novel theoretical framework to obtain and analyse opinions from 'Establishment' and 'Local Government Officials' (LGO) samples as to whether and how to promote greater inclusion.